Un(der)served: Factors influencing microinsurance penetration in Zambia - Siloya, Perpetua (Graduate School of Business (GSB), 2023)
The low-income population continue to be un(der)served when it comes to provision of formal insurance services in Zambia. This is despite the informal sector forming a significant pool of at least 63.5 percent of the total workforce (ZSA, 2020) and microinsurance development attracting widespread interest from local and international organisations. To understand the factors influencing microinsurance penetration in Zambia, using a tailored conceptual framework, this research employs a purposive random sampling and semi-structured interviews to collect data from fourteen (14) participants from the supply-side comprising insurance companies, InsurTech organisations, and non-distribution providers with fifteen (15) consumers for the demand-side. A thematic analysis framework was used to analyse the data. The findings reveal that while some factors have positively influenced microinsurance penetration; others have negatively influenced it. On the supply side, using partnerships and enhancing technology supports distribution. Applying the Ansoff Growth Theory, the study finds that insurance service providers adopt diversification and product development strategies that are unique to microinsurance. Some factors have negatively influenced microinsurance penetration. On the supply side, a lack of historical information has resulted in issues with information asymmetry while the low claims ratio is attributed to the infancy of the microinsurance market. In addition, the cash nature of the industry has caused premium collection challenges leading to high lapse rates. On the demand side the poor insurance knowledge, macroeconomic indicators such as inflation, effects of COVID – 19 resulting in loss of income, lack of understanding of product benefits, low levels of trust of insurance providers have negatively influenced microinsurance penetration the demand-side. Lastly, the findings around consumers' attitudes to risk were inconclusive, with moral hazard not widespread. The study recommends that insurance providers strengthen mutually beneficial partnerships and collectively enhance insurance awareness. The government needs to facilitate hard and soft infrastructure in many rural areas for better accessibility. The Technical Advisory Group for Microinsurance (TAG) should coordinate the creation of a centralised database that can be used to store customer details to manage information asymmetry.